2010
DOI: 10.1111/j.1472-765x.2010.02941.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular ethanol accumulation in yeast cells during aerobic fermentation: a Raman spectroscopic exploration

Abstract: Aims:  To investigate the intracellular ethanol accumulation in yeast cells by using laser tweezers Raman spectroscopy (LTRS). Methods and Results:  Ethanol accumulation in individual yeast cells during aerobic fermentation triggered by excess glucose was studied using LTRS. Its amount was obtained by comparing intracellular and extracellular ethanol concentrations during initial process of ethanol production. We found that (i) yeasts start to produce ethanol within 3 min after triggering aerobic fermentation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…Thus, other techniques have included Raman spectroscopy for the chemical imaging of productive clones, 793,794 while IR spectroscopy has been used to assess secondary structure ( i.e. folding).…”
Section: Screeningmentioning
confidence: 99%
“…Thus, other techniques have included Raman spectroscopy for the chemical imaging of productive clones, 793,794 while IR spectroscopy has been used to assess secondary structure ( i.e. folding).…”
Section: Screeningmentioning
confidence: 99%
“…In ethanol fermentation, it must be prevented that ethanol is stored intra-cellular, because it influences the viability of yeasts. Raman spectroscopy is considered a suitable, reagent-free tool to monitor and study process kinetics in ethanol fermentation as it was shown to be sensitive enough to detect intracellular ethanol accumulation in yeasts by the ethanol-specific Raman band near 881 cm –1 [36, 37]. Intracellular-produced fatty acids were also detectable using Raman spectroscopy.…”
Section: Raman Spectroscopy and Its Application In Microbiology Andmentioning
confidence: 99%
“…In these experiments, oxidative stress due to 619 exposure to hydroxyl radicals was induced in RBCs. Cells exposed to 620 these radicals were found to show increased intensities in Raman [72]. Also, the rapid assessment of oxidative stress 634 response of single yeast cells was demonstrated by Chang et al [73].…”
Section: Introductionmentioning
confidence: 92%